2001
DOI: 10.1182/blood.v97.11.3484
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells/basophils in the peripheral blood of allergic individuals who are HIV-1 susceptible due to their surface expression of CD4 and the chemokine receptors CCR3, CCR5, and CXCR4

Abstract: IntroductionMast cells (MCs) and basophils are histamine-containing, metachromatic granulocytes that express the high-affinity IgE receptor, Fc⑀RI, on their surfaces. 1,2 When activated via this receptor, both populations of cells immediately exocytose their granule constituents and then more slowly generate and release cytokines, chemokines, and arachidonic acid metabolites. Thus, these granulocytes play extremely important roles in IgE-mediated inflammatory responses. Although human MCs and basophils are sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 61 publications
2
55
0
Order By: Relevance
“…Together, these events could provide a mechanism through which CD4 directly modulates CD8 ϩ CTL function. Interestingly, the CD4 molecule has been found, under various conditions, on a subset of hematopoietic progenitor cells (28,29), B cells (30), NK cells (31), eosinophils (32), monocytes (33), neutrophils (34), mast cells͞basophils (35), and microglia (36). Our current studies specifically examine the function of CD4 only on purified CD8 ϩ T cells, and further studies are required to fully define the complex role that this molecule plays in the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these events could provide a mechanism through which CD4 directly modulates CD8 ϩ CTL function. Interestingly, the CD4 molecule has been found, under various conditions, on a subset of hematopoietic progenitor cells (28,29), B cells (30), NK cells (31), eosinophils (32), monocytes (33), neutrophils (34), mast cells͞basophils (35), and microglia (36). Our current studies specifically examine the function of CD4 only on purified CD8 ϩ T cells, and further studies are required to fully define the complex role that this molecule plays in the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…ϩ cells could be involved in HIV-1 infection in a variety of ways (11)(12)(13)(14)(15)(16). In fact, we have demonstrated that gp120 from divergent HIV-1 isolates from different clades interacts with the V H 3 region of IgE on human Fc⑀RI ϩ (9, 47).…”
Section: Increasing Evidence Indicates That Human Fc⑀rimentioning
confidence: 99%
“…Moreover, Tat protein up-regulates the level of CCR3 mRNA and surface expression of CCR3 on human basophils (10). Recent evidence suggests that a population of basophils and/or mast cells in peripheral blood can be infected in vitro by M-tropic strains of HIV-1 (11,12). Consequently, human Fc⑀RI ϩ cells are important in HIV-1 infection (13)(14)(15)(16).…”
Section: T He Human Immunodeficiency Viruses Hiv-1 and Hiv-2 Destroy Cd4mentioning
confidence: 99%
See 1 more Smart Citation
“…Although these and other findings document that MCs play beneficial immunosurveillance and effector roles in the body, it has been known for some time that MCs also exhibit adverse roles in numerous inflammatory disorders including asthma, chronic urticaria, and systemic anaphylaxis. Recent studies (7)(8)(9) have revealed that these effector cells also participate in the pathogenesis of AIDS.…”
Section: Mast Cells (Mcs)mentioning
confidence: 99%